Step 1) subtract 8p on both sides of the equation.
5p - 14 = 8p + 4
-8p -8p
5p - 8p will equal -3. 8p - 8p cancels out.
Step 2) Bring the rest of the equation down.
-3p - 14 = 4
Step 3) Add 14 to both sides of the equation.
-3p - 14 = 4
+14 +14
-14 abs +14 cancel out. 4 + 14 equals 18.
-3p = 18
Step 4) Divide -3 on both sides.
-3p/-3 = 18/-3
-3 and -3 cancel out. And 18 divided by -3 = -6.
So your final answer would be p = -6.
I hope this helped, let me know if you have any more questions on this :)